Effect of nutritonal therapy on Helicobacter pylori infections in severely malnourished children - Mahdin A. Husaini; Jajah K. Husaini; Susie Suwarti; Yekti Widodo Heryudarini Harahap (Paediatrica Indonesiana, 2010)
Background Severe malnutrition young children has been a problem in Indonesia for many years. In recent years the condition may be increasing. Besides a lack of nutrition, H. pylori infection may contribute to this condition.Objective To determine if severely malnourished children have high rates of H. pylori infection, and to test if improving nutritional deficiency by drinking skimmed milk can reduce the number of H. pylori cases.Methods A total of 83 children aged 6 - 36 months with severe malnutrition (weight-for-age < -3 Z-scores), who were outpatients at the Nutrition Clinic in fugor served as subjects for this longitudinal study. Out of 83 children, 42 subjects (50%) tested positively for H. pylori infection (Group P) and 41 subjects Â (49.4%) tested negatively (Group NP). All subjects received the same nutritional intervention consisting Â of medical care, 250 g of skimmed milk, and guidance concerning proper feeding and care of children at every clinic visit, for a duration of 6 months.Results The study revealed that after 6 months of nutritional intervention, the percentage of children suffering from diarrhea was significantly (P < 0.05) reduced in Group P, while no significant change was demonstrated in Group NP. The nutritional intervention also demonstrated a noticeable effect on the incidence of H pylori infection, reducing the number of H. pylori infections by 29% in Group P. In Group Np, 100% of the children remained free of H. pylori infection after intervention. No new cases of H. pylori infection appeared in either group. An improvement in nutritional status was also observed: 23.8% of severely undernourished children in Group P and 3 4.1 % in Group NP improved after intervention.Conclusion Drinking skimmed milk twice daily, as well as parental counseling on proper feeding and child care, led to improved nutritional status of severely malnourished children. We also observed that skimmed (non-fat) milk may have a role in preventing and treating malnourished children with H. pylori infection.